Antidumping Mechanisms and Safeguards in Peru - Webb, Richard (World Bank, Washington, DC, 2012)
Peru's experience in the application of antidumping and safeguard measures is characterized by a radical change in the philosophy and procedures of trade at the beginning of the 1990s, and by an increasing use of these mechanisms. Trade liberalization was accompanied by the liberalization of foreign currency transactions and of financial and labor markets. Also, the internal revenue administration was modernized, institutions for regulation and competition defense were created, and state enterprises were transferred to private owners or concessionaires. New laws and institutions were created to regulate markets, including INDECOPI, a novel government agency charged with antimonopoly regulation and consumer defense, and which houses the Antidumping and Subsidies Commission. This highly autonomous and technical Commission became the central player in the implementation of WTO rules and procedures for fair trade. Since the reform was launched, a total of 81 trade protection cases have been presented, of which 57 were followed by a dumping investigation. The application of antidumping duties was approved for 29 of the cases investigated. Only two cases of safeguard investigations were recorded, one of which (Chinese textile clothing articles) is still in the negotiation phase. This paper reviews that case experience in detail, concluding that Peru has clearly differentiated between unfair competition and dumping on the one hand, and damage and safeguards on the other, and has applied strict technical criteria to the former and broader political considerations to the latter. Despite recent indications of a partial retreat from those principles, the decade-old reform is expected to last.